AÇIK KALP CERRAHİSİNDE, HEPARİN DOZU VE SERBEST PLAZMA HEMOGLOBİNİ ARASINDAKİ İLİŞKİ - USLU, Atilla; YİĞİT, Refik (Cerrahpaşa Medical Journal, 2019)
Background and Design.- New equipments and methods which will be crucial in decreasing hemolyze rate have been experienced for the last years. For this reason, the equipments that are used in cardiopulmonary bypass (CPB) must show similarities to biological tissues. That.s because, those equipments must be coated with immobilize heparin and thus it must be worked for gaining them similar attributes with vessel endothel. The aim is to decrease the mortality rate of operation incidence by decreasing contraindications result from CPB. 1) In the operations that make up the control group, full dose of systemic heparinization (4,0 mg/kg) with uncoated CPB system (UCS) was used. 2) In the experiment group, low dose systemic heparinization (1,5 mg/kg) with heparin coated CPB system (HCS) was used. Results.- By taking the levels of free plasma hemoglobin (FpHb) in to consideration, the differences occurred in different stages within each group and the differences in same stages between opponent groups were observed. In both HCS, UCS, and 30 mins after the operation, FpHb level started to gradually increase from the preoperative period level. In HCS, FpHb level stayed constants from the beginning of the third period, and it decreased to period level after the fifth stage. In UCS, the level increased excessively until the forth period and then the level decreased gradually. Conclusion.- FpHb levels of the UCS group were found to be statistically significantly higher than the HCS group in every stages of the than stage 1. (p<0.05).